Bright silicon vacancy centers in diamond/SiC composite films synthesized by a MPCVD method. (January 2021) - Yang, Bing; Li, Haining; Yu, Biao; Lu, Jiaqi; Huang, Nan; Liu, Lusheng; Jiang, Xin
Abstract: SiC is always produced forming diamond/SiC composite films owing to the oversaturated doping of Si atoms during the preparation of high emission SiV centers. As a higher refractive index material (n = 2.72), the presence of SiC could possibly lead to inefficient photo-luminescent (PL) collection of SiV centers with total internal reflection. In order to understand such effect, different diamond/SiC films were deposited in a 915 MHz microwave plasma CVD (MPCVD) using the reactive gas of tetramethylsilane (TMS). The microstructure and photoluminescence of SiV centers were systematically investigated. It is found that the addition of TMS gas leads to the formation of cubic β-SiC and the refinement of diamond crystals. At the TMS gas flow of 5 sccm, the concentration of β-SiC is about 10% and the average diamond size is about 98 nm. The film exhibits the optimized PL emission of SiV centers, with the ratio of SiV PL to diamond Raman peak being 21.4. Increasing TMS gas flow leads to the increase of the concentration of β-SiC and the deterioration of PL emission of SiV centers. These results reveal that the introduction of TMS gas at a low flow advances the formation of diamond/SiC film containing high-brightness SiV centers. Graphical abstract: The diamond/SiC composite film at SiC concentration of 10% exhibits the optimized PL collection of SiV centers (the 2# sample). Image 1